Identification of a novel mutation of sat (Gly82Arg) in Shigella flexneri serotype 7a: insights into clinical relevance - Iqbal Nisa; Muhammad Qasim; Arnold Driessen; Jeroen Nijland; Hazir Rahman; Yasar Mehmood Yousafzai; Khalid J. Alzahrani; Jochen Mattner; Niaz Muhammad; Fazli Bari; Taj Ali Khan (Folia Microbiologica, 2026)

Exploration of medicinal and nutritional value of Himalayan wild edible fruits: implications for sustainable health and functional foods - Syeda Khateeb Fatima; Rizwan Taj Khan; Munazza Nazir; Muhammad Manzoor; Syed Waseem Gillani; Mumna Munir; Muhammad Nasir; Wasim Akhtar; Shabir Ahmad; Manal Abdulaziz Binobead; M Ajmal Ali (Genetic Resources and Crop Evolution, 2025)

Detection and insight into structural requirements of SARS_CoV2 antibodies by peptide- oligonucleotides derived from sunflower trypsin inhibitor 1 (SFTI-1) peptide - Sunithi Gunasekera; Hongxing Zhao; Camilla Eriksson; Mingshu Zhang; Taj Muhammad; Ulf Landegren; Ulf Göransson (Phytochemistry Letters, 2025)

Harnessing the constrained macrocyclic peptide frameworks for the development of antimicrobial peptides to treat infections - Taj Muhammad; Sunithi Gunasekera; John Kerr White; Adam A. Strömstedt; Soumitra Mohanty; Anna Blasi-Romero; Carlos Palo-Nieto; Natalia Ferraz; Annelie Brauner; Ulf Göransson (Phytochemistry Letters, 2025)

Peptide discovery and development – known and dark matter - Ulf Göransson; Taj Muhammad; Erik Jacobsson; Luke Robertson; Blazej Slazak; Sunithi Gunasekera (Phytochemistry Letters, 2025)

Antibacterial activity and mechanism of novel phage endolysin lysSEP21 against dual-species biofilm of Salmonella and Escherichia coli and its application in food preservation - Muhammad Imran Taj; Peng Guan; Yifeng Ding; Xinyuan Zheng; Weiying Kong; Xiaohong Wang (International Journal of Food Microbiology, 2025)

Evaluation of groundwater quality of Mirpurkhas District, Sindh, Pakistan, for drinking, irrigation and multivariate analysis - Asadullah Khaskheli; Taj Muhammad Jahangir Khuhawar; Muhammad Yar Khuhawar; Faheem Yar Khuhawar; Muhammad Farooque Lanjwani; Abdul Qayoom Landar (Arabian Journal of Geosciences, 2025)

Synthesis and Antibacterial Studies of Silver Loaded TiO2 Electrospun Nanofibers Against E. coli by Fluorescence Spectroscopy and Microscopy - Bisma Khanam; Rafaqat Ali Khan; Shahzad Anwar; Hina Ali; Muhammad Zakria; Taj Muhammad Khan; A. Rahman; Ahmad Adnan; Nida Ali Shan; Muhammad Raffi (Journal of Fluorescence, 2025)

Development of a dispersive liquid–liquid microextraction technique for ultra-sensitive detection of gold in environmental samples using atomic absorption spectrometry - Waheed Ali Soomro; Muhammad Yar Khuhawar; Taj Muhammad Jahangir; Muhammad Farooque Lanjwani; Zulfiqar Ali Bhatti; Rafi-u-Zaman Brohi; Imran Khan Rind (Environmental Monitoring and Assessment, 2025)

Assessing the physicochemical properties of surface/groundwater of Sudhnoti district, Azad Jammu and Kashmir: Impacts on lindane degradation by photocatalysis - Taj Ur Rahman; Lubna Saba; Ashraf Ali; Wajiha Liaqat; Sanaullah Khan; Javed Ali Khan; Muhammad Aurang Zeb; Sajjad Hussain; Eman Y. Santali; Changseok Han (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Biocontrol characteristics and application of phage SEP4 against multidrug-resistant Salmonella biofilm on food matrix - Muhammad Imran Taj; Yifeng Ding; Yuexin Bao; Yingjie Huang; Peng Guan; Yiming Zhang; Xi Liu; Zixin Ming; Xiaohong Wang (Food Bioscience, 2024)

Risk identification of salts and heavy metals in water by multivariate statistical techniques and GIS based interpolation: A case study of Saeedabad, Sindh, Pakistan - Imran Khan Rind; Muhammad Yar Khuhawar; Taj Muhammad Jahangir; Najma Memon; Ahsan Habib; Muhammad Farooque Lanjwani; Waheed Ali Soomro; Ghamshan Suther; Wenbin Liu (Regional Studies in Marine Science, 2024)

Comparative role of charcoal, biochar, hydrochar and modified biochar on bioavailability of heavy metal(loid)s and machine learning regression analysis in alkaline polluted soil - Altaf Hussain Lahori; Samreen Riaz Ahmed; Monika Mierzwa-Hersztek; Madiha Afzal; Ambreen Afzal; Shella Bano; Maria Taj Muhammad; Aqsa Aqsa; Viola Vambol; Sergij Vambol (Science of The Total Environment, 2024)

Utilizing thiourea-modified biochars to mitigate toxic metal pollution and promote mustard (Brassica campestris) plant growth in contaminated soils - Irfan Saleem; Samreen Riaz Ahmed; Altaf Hussain Lahori; Monika Mierzwa-Hersztek; Shella Bano; Ambreen Afzal; Maria Taj Muhammad; Madiha Afzal; Viola Vambol; Sergij Vambol; Zengqiang Zhang (Journal of Geochemical Exploration, 2024)

Phytochemical screening and antimicrobial potential of Chenopodium quinoa extract against pathogenic bacterial strains - Hina Anwar; Arslan Habib; Muhammad Usman Taj; Muhammad Azhar Ali; Ayesha Munir; Marva Shafi; Maria Saddique; Sohaib Ahmed; Henrique D. M. Coutinho (Vegetos, 2024)

Water quality index and geographic information system to assess the groundwater quality of taluka Matiari, Sindh, Pakistan - Imran Khan Rind; Muhammad Yar Khuhawar; Taj Muhammad Jahangir; Najma Memon; Muhammad Farooque Lanjwani; Waheed Ali Soomro (Arabian Journal of Geosciences, 2024)

Biogenic adsorbents for removal of drugs and dyes: A comprehensive review on properties, modification and applications - Mobeen Ur Rehman; Muhammad Babar Taj; Sónia A.C. Carabineiro (Chemosphere, 2023)

Spatial variability and hydrochemical quality of groundwater of Hyderabad Rural, Sindh, Pakistan - Laeeq Ahmed Khan Khokhar; Muhammad Yar Khuhawar; Taj Muhammad Jahangir Khuhawar; Muhammad Farooque Lanjwani; Ghulam Murtaza Arain; Faiz Muhammad Khokhar; Mezhar Iqbal Khaskheli (Sustainable Water Resources Management, 2023)

Gum-based nanocomposites for the removal of metals and dyes from waste water - Muhammad Usman; Muhammad Babar Taj; Sónia Alexandra Correia Carabineiro (Environmental Science and Pollution Research, 2023)
The importance of water for all living organisms is unquestionable and protecting its sources is crucial. In order to reduce water contaminants, like toxic metals and organic dyes, researchers are exploring different techniques, such as adsorption, photocatalytic degradation, and electrolysis. Novel materials are also being sought. In particular, biopolymers like guar gum and xanthan gum, that are eco-friendly, non-toxic, reusable, abundant and cost-effective, have enormous potential. Gum-based nanocomposites can be prepared and used for removing heavy metals and colored dyes by adsorption and degradation, respectively. This review explains the significance of gum-based nanomaterials in waste water treatment, including preparative steps, characterization techniques, kinetics models, and the degradation and adsorption mechanisms involved.

Correction to: Spatiotemporal assessment of the hydrometeorology in a transboundary Kabul River Basin - Mahmood Alam Khan; Muhammad Shahzad Khattak; Muhammad Ajmal; Taj Ali Khan (Arabian Journal of Geosciences, 2023)

Spatiotemporal assessment of the hydrometeorology in a transboundary Kabul River Basin - Mahmood Alam Khan; Muhammad Shahzad Khattak; Muhammad Ajmal; Taj Ali Khan (Arabian Journal of Geosciences, 2023)

Impact of rock-water interaction on hydrogeochemical characteristics of groundwater: Using multivariate statistical, water quality index and irrigation indices of chachro sub-district, thar desert, sindh, Pakistan - Muhammad Soomar Samtio; Asghar Ali alias Daahar Hakro; Taj Muhammad Jahangir; Abdul Shakoor Mastoi; Muhammad Farooque Lanjwani; Riaz Hussain Rajper; Rafique Ahmed Lashari; Muhammad Hassan Agheem; Muhammad Waseem Noonari (Groundwater for Sustainable Development, 2023)

Prosperity risk assessment by heavy metal contamination on human health and multivariate statistical analysis of groundwater as a drinking source - Laeeq Ahmed Khan Khokhar; Muhammad Yar Khuhawar; Taj Muhammad Jahangir; Ghulam Murtaza Arain; Faiz Muhammad Khokhar; Mazhar Iqbal Khaskheli; Shaishta Khan; Muhammad FarooqueLajwani; Muhammad Ilyas Abro; Zahid Ali Zounr (Arabian Journal of Geosciences, 2023)

Spatial variability of hydrochemistry and health risk assessment of groundwater of taluka Hala, district Matiari, Sindh, Pakistan - Imran Khan Rind; Muhammad Yar Khuhawar; Muhammad Farooque Lanjwani; Taj Muhammad Jahangir Khuhawar; Muhammad Soomar Samtio; Waheed Ali Soomro; Abdul Rehman Baloch (Arabian Journal of Geosciences, 2023)

Taxonomy and distribution of butterfly fauna of family pieridae (lepidoptera) in district abbottabad, Khyber Pakhtunkhwa, Pakistan - Sidra Taj; Shoaib Ali; Shabir Ahmed; Muhammad Ather Rafi; Sardar Azhar Mehmood; Muzafar Shah (International Journal of Tropical Insect Science, 2022)

Antimicrobial Resistance of Shigella flexneri in Pakistani Pediatric Population Reveals an Increased Trend of Third-Generation Cephalosporin Resistance - Iqbal Nisa; Mohammad Haroon; Arnold Driessen; Jeroen Nijland; Hazir Rahman; Nusrat Yasin; Mubashir Hussain; Taj Ali Khan; Amjad Ali; Saeed Ahmad Khan; Muhammad Qasim (Current Microbiology, 2022)

Spatial distribution of hydrochemistry and characterization of groundwater of taluka Bakrani, Larkana, Sindh, Pakistan - Muhammad Farooque Lanjwani; Muhammad Yar Khuhawar; Taj Muhammad Jahangir Khuhawar; Saima Qayoom Memon; Muhammad Soomar Samtio; Abdul Hameed Lanjwani; Imran Khan Rind (Arabian Journal of Geosciences, 2022)

A novel protein truncating mutation in L2HGDH causes L-2-hydroxyglutaric aciduria in a consanguineous Pakistani family - Muhammad Muzammal; Muhammad Zeeshan Ali; Beatrice Brugger; Jasmin Blatterer; Safeer Ahmad; Sundas Taj; Syed Khizar Shah; Saadullah Khan; Christian Enzinger; Erwin Petek; Klaus Wagner; Muzammil Ahmad Khan; et al. (Metabolic Brain Disease, 2022)
Background L-2-hydroxyglutaric aciduria (L2HGA) is a rare neurometabolic disorder that occurs due to accumulation of L-2-hydroxyglutaric acid in the cerebrospinal fluid (CSF), plasma and urine. The clinical manifestation of L2HGA includes intellectual disability, cerebellar ataxia, epilepsy, speech problems and macrocephaly. Methods In the present study, we ascertained a multigenerational consanguineous Pakistani family with 5 affected individuals. Clinical studies were performed through biochemical tests and brain CT scan. Locus mapping was carried out through genome-wide SNP genotyping, whole exome sequencing and Sanger sequencing. For in silico studies protein structural modeling and docking was done using I-TASSER, Cluspro and AutoDock VINA tools. Results Affected individuals presented with cognitive impairment, gait disturbance, speech difficulties and psychomotor delay. Radiologic analysis of a male patient revealed leukoaraiosis with hypoattenuation of cerebral white matter, suggestive of hypomyelination. Homozygosity mapping in this family revealed a linkage region on chromosome 14 between markers rs2039791 and rs781354. Subsequent whole exome analysis identified a novel frameshift mutation NM_024884.3:c.180delG, p.(Ala62Profs*24) in the second exon of L2HGDH . Sanger sequencing confirmed segregation of this mutation with the disease phenotype. The identification of the most N-terminal loss of function mutation published thus far further expands the mutational spectrum of L2HGDH.

Inducible knockdown of Mycobacterium smegmatis MSMEG_2975 (glyoxalase II) affected bacterial growth, antibiotic susceptibility, biofilm, and transcriptome - Muhammad Haris; Changming Chen; Jing Wu; Muhammad Noman Ramzan; Ayaz Taj; Shanshan Sha; Hayan Ullah; Yufang Ma (Archives of Microbiology, 2022)

Impact of water–sediment interaction on hydrogeochemical signature of dug well aquifer by using geospatial and multivariate statistical techniques of Islamkot sub-district, Tharparkar district, Sindh, Pakistan - Muhammad Soomar Samtio; Khadim Hussain Rajper; Asghar Ali alias Daahar Hakro; Muhammad Farooque Lanjwani; Abdul Qayoom Mughari; Rakhshanda Sadaf; Riaz Hussain Rajper; Abdul Shakoor Mastoi; Muhammad Hassan Agheem; Rafique Ahmed Lashari; Taj Muhmmad Jahangir (Arabian Journal of Geosciences, 2022)

Determination of pesticide residues in dates using UHPLC-QqQ-MS/MS: method development and validation - Somia Qayyum; Touqeer Taj; Muhammad Tauseef; Muhammad Ishtiaq; Nazia Rafique; Karam Ahad; Muhammad Aslam Mirza; Muhammad Aziz Choudhary; Farrakh Mehboob (Environmental Monitoring and Assessment, 2021)

Epidemiology of molecular probes in Xpert MTB/RIF assay in Khyber Pakhtunkhwa, Pakistan - Anwar Sheed Khan; Muhammad Tahir Khan; Sajid Ali; Taj Ali Khan; Muhammad Qasim; Arif Malik; Sajid Ali; Wasim Sajjad; Qurrat ul ain; Muhammad Irfan (Archives of Microbiology, 2021)

Health risk assessment of chromium contamination in the nearby population of mining plants, situated at Balochistan, Pakistan - Tasawar Ali Chandio; Mohammad Nasiruddin Khan; Maria Taj Muhammad; Ozcan Yalcinkaya; Eylem Turan; Ahmet Furkan Kayis (Environmental Science and Pollution Research, 2021)

Synthesis of novel nicotinamide susbstituted phthalocyanine and photodynamic antomicrobial chemotherapy evaluation potentiated by potassium iodide against the gram positive S. aureus and gram negative E. coli - Azeem Ullah; Tingkai Zhao; Munira Taj Muhammad; Muhammad Khan; Saira Qurban; Abdul Rahman; Ishaq Ahmad (Biotechnology Letters, 2021)

Fluoride and arsenic contamination in drinking water due to mining activities and its impact on local area population - Tasawar Ali Chandio; Muhammad Nasiruddin Khan; Maria Taj Muhammad; Ozcan Yalcinkaya; Agha Arslan Wasim; Ahmet Furkan Kayis (Environmental Science and Pollution Research, 2021)

Molecular epidemiology of Shigella flexneri isolated from pediatrics in a diarrhea-endemic area of Khyber Pakhtunkhwa, Pakistan - Iqbal Nisa; Muhammad Qasim; Arnold Driessen; Jeroen Nijland; Fazli Bari; Mohammad Haroon; Hazir Rahman; Nusrat Yasin; Taj Ali Khan; Mubbashir Hussain; Waheed Ullah (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Novel nonsense IL-12Rβ1 mutation associated with recurrent tuberculosis - Noor ul Akbar; Shahid Niaz Khan; Muhammad Usman Amin; Muhammad Ishfaq; Otavio Cabral-Marques; Lena F Schimke; Asif Iqbal; Ikram Ullah; Mubashir Hussain; Ijaz Ali; Nasar Khan; Nadia El Khawanky; et al. (Immunologic Research, 2019)

Modeling Sugar Beet Response to Different Combinations of On-Farm Water Management Practices Under Semi-arid Sub-tropical Environment - Abdul Malik; Abdul Sattar Shakir; Muhammad Jamal Khan; Muhammad Ajmal; Muhammad Shahzad Khattak; Taj Ali Khan; Zia Ul Haq; Mahmood Alam Khan; Naeem Ijaz (Sugar Tech, 2019)

Biochar for sustainable soil and environment: a comprehensive review - Niaz Muhammad; Mubashir Hussain; Waheed Ullah; Taj Ali Khan; Shafaqat Ali; Ali Akbar; Rukhsanda Aziz; Muhammad Khalid Rafiq; Robert Thomas Bachmann; Mohammad I. Al-Wabel; Muhammad Rizwan (Arabian Journal of Geosciences, 2018)

Water quality assessment of Ramser site, Indus Delta, Sindh, Pakistan - Muhammad Yar Khuhawar; Rafi O. Zaman Brohi; Taj Muhammad Jahangir; Muhammad Farooque Lanjwani (Environmental Monitoring and Assessment, 2018)

Impact of grazing on soil, vegetation and ewe production performances in a semi-arid rangeland - Muhammad Islam; Abdul Razzaq; Shamim Gul; Sarfraz Ahmad; Taj Muhammad; Sawsan Hassan; Barbara Rischkowsky; M. N. M. Ibrahim; Mounir Louhaichi (Journal of Mountain Science, 2018)

Assessment of AquaCrop Model in Simulating Sugar Beet Canopy Cover, Biomass and Root Yield under Different Irrigation and Field Management Practices in Semi-Arid Regions of Pakistan - Abdul Malik; Abdul Sattar Shakir; Muhammad Ajmal; Muhammad Jamal Khan; Taj Ali Khan (Water Resources Management, 2017)

Prevalence of Waterborne Diseases in Exposed and Unexposed Clusters Using Biosand Filters in a Rural Community, Sindh, Pakistan - Munir Ahmed Sheikh; Muhammad Ayaz Mustufa; Taj Muhammad Laghari; Binafsha Manzoor; Syed Ali Haider; Safia Bibi; Firdous Imran Ali (Exposure and Health, 2016)

Determination of arsenic contents in groundwater of District Rahim Yar Khan Southern Punjab, Pakistan - Muhammad Tariq Mahar; Muhammad Yar Khuhawar; Taj Muhammad Jahangir; Mushtaq Ahmad Baloch (Arabian Journal of Geosciences, 2015)

Water quality and sediment assessment of Manchar Lake, Sindh, Pakistan: after effects of the super flood of 2010 - Taj Muhammad Jahangir; Muhammad Yar Khuhawar; Sultan Mahmood Leghari; Muhammad Tariq Mahar; Khalida Parveen Mahar (Arabian Journal of Geosciences, 2015)